Study of indications, complications and outcomes of neonatal transport by a skilled team - Mohan, Karthik Ram; Kumar, Rajesh (International Journal of Contemporary Pediatrics, 2019)
Background: A skilled transport team is an essential requirement for safe and effective neonatal transport. The transport team of this level III NICU in Chennai performs a considerable number of transports every year and a need was felt to study the indications, complications and outcomes of transport. Methods: Prospective Descriptive study of neonatal transports conducted 18 months Patients were divided into 2 main groups based on transport Duration: Short (≤1hr) and Long (>1hr) transport groups. TRIPS (Transport risk index of physiologic stability) score, a risk- weighted validated neonatal transport was used as a practical system for assessing infant transport care Results: During the study period 210 transports were performed from 12 cities and towns. 60% transports were of short duration. Respiratory causes were the most common indications (43.8%) followed by CNS causes (19.5%). 44.3%(93) patients required ventilation during the transport process. Overall, there was improvement in mean TRIPS 2 score compared to TRIPS 1 in all groups of patients (Short, Prolonged, Survivors and Non-survivors). Total mortality of transported group was 31 patients (14.8%). (Including 02 patients who died enroute). There were non-significant differences in 7 day mortality (7.6% vs 8.4%) and total mortality (13.9% vs 13.4%) between the groups. Complications that occurred during transport included hyperglycemia, prolonged CFT, hypothermia, accidental extubation enroute, hypoglycemia, hyperthermia, Hypotension, and persistent Hypoxia. Conclusions: It appears, that overall, duration of transport does not adversely affect outcome. Transport Team should be able to intubate and ventilate the baby and diagnose and manage complications like hypothermia, shock and hypoglycemia at referring hospital and enroute.